The digital simulation of a turbo-charged diesel engine - Shroff, H. D.; Hodgetts, D. (College of Aeronautics, 1969)
A mathematical simulation of a six cylinder four stroke water cooled diesel engine is described and then used to study the changes in performance caused by variations of engine paramters and operating conditions. The results are discussed with reference to the mathematical model employed and the physical system. A limited study, to demonstrate the applicability of the simulation, considers the optimisation of a variable geometry system to achieve a performance target.